Selecting Portable Ankle/Toe Brachial Pressure Index Systems for a Peripheral Arterial Disease Population Screening Programme: a Systematic Review, Clinical Evaluation Exercise, and Consensus Process. (December 2022) - Watson, Emma L.; Patel, Bhavisha; Katsogridakis, Emmanuel; Pepper, Coral J.; Messeder, Sarah Jane; Saratzis, Athanasios; Zubair, Maria; Nicholls, Jennifer K.; Chung, Emma; Bown, Matthew J.
Abstract : Objective: To provide an overview of systems available for peripheral arterial disease (PAD) screening, together with respective accuracies and a clinical evaluation to identify a system suitable for use in a community screening programme. Methods: A systematic review of the diagnostic accuracy of six ankle brachial pressure index (ABPI) and toe brachial pressure index (TBPI) devices deemed to be portable, which were Conformité Européenne (CE) marked, and were automated or semi-automated was carried out compared with gold standard handheld Doppler and duplex ultrasound. The devices were MESI-ABPI-MD, Huntleigh Dopplex Ability, Huntleigh ABPI and TBPI systems, Systoe TBPI system, and BlueDop. Seven databases (MEDLINE, EMBASE, Scopus, Web of Science, Cochrane Database of Systematic Reviews, Cochrane Register of Controlled Trials (CENTRAL), and Cumulative Index to Nursing and Allied Health Literature (CINAHL)) were searched, and 11 studies were identified as eligible for review. This was followed by hands on clinical evaluation by abdominal aortic aneurysm (AAA) screening staff ( n = 39). During this, devices were demonstrated to staff which they then tested on volunteers and gave feedback using pre-designed questionnaires on their suitability for use in a screening programme. Finally, accuracy data and staff preferences were combined during a consensus conference that was held between study and screening staff to determine the most appropriate device to use in a community screening programme. Results: Generally, the evaluated systems have a moderate level of sensitivity and a high level of specificity: Dopplex ability sensitivity 20% – 70%, specificity 86% – 96%; MESI sensitivity 57% – 74%, specificity 85% – 99%; BlueDop sensitivity 95%, specificity 89%; and Systoe sensitivity 71%, specificity 77%. Clinical evaluation by screening staff identified a preference for the MESI system. The consensus conference concluded that the MESI device was a good candidate for use in a community PAD screening programme. Conclusion: The MESI system is a good candidate to consider for community PAD screening.